Long Atrial Fibrillation Duration and Early Recurrence Are Reliable Predictors of Late Recurrence After Radiofrequency Catheter Ablation - Li, Zhitong; Wang, Shihao; Hidru, Tesfaldet H.; Sun, Yuanjun; Gao, Lianjun; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2022)
Background: Recurrence after atrial fibrillation (AF) ablation is still common. Objective: This study aimed to evaluate the predictive abilities of AF duration and early recurrence to discriminate high-risk patients for recurrence. Methods: We enrolled 1763 consecutive AF patients who were scheduled to receive the index radiofrequency catheter ablation (RFCA) from January 2016 to August 2021 in Dalian, China. Long AF duration (LAFD) was considered if the course of AF lasted ≥ 12 months. Early recurrence (ER) was defined as any atrial tachycardia (AT) or AF event longer than 30 seconds occurring within 3 months post-RFCA. Results: Late recurrence occurred in 643 (36.5%) of the 1763 patients at a median of 35 months after RFCA. Multivariate analysis identified LAFD (HR: 1.80, 95% CI: 1.38–2.35, P< 0.001) and ER (HR: 2.34, 95% CI: 1.82–3.01, P< 0.001) as strong independent predictors of late recurrence in non-paroxysmal AF. Likewise, LAFD (HR: 1.48, 95% CI: 1.20–1.84, P< 0.001) and ER (HR: 3.40, 95% CI: 2.68-4.30, P< 0.001) was significantly associated with late recurrence in paroxysmal AF. Receiver operating curve analyses revealed that the CAAP-AF had the highest predict power(AUC 0.586). The addition of ER and LAFD to the CAAP-AF score significantly improved risk discrimination for late recurrence after AF ablation from 0.586 to 0.686. Conclusions: LAFD and ER were independently associated with late recurrence. The prediction performance of the CAAP-AF model for recurrence was improved by the addition of LAFD and ER.